Modulation of IL-10/IL-10R expression by mafosfamide, a derivative of 4-hydroxycyclophosphamide, in a rat B-cell lymphoma - Rico, María José; Matar, Pablo; Scharovsky, O. Graciela (Sociedad Latinoamericana de Microscopía Electrónica. Centro Regional de Investigaciones Científicas y Tecnológicas (Mendoza, Argentina), 2012)
We have already shown that IL-10 plays an important role in immunosuppression and metastatic dissemination in the rat B-cell lymphoma L-TACB model. It was suggested that the up-regulation of IL-10 production and IL-10 receptor (IL-10R) expression would be part of the transition from primary tumor to metastatic phenotype and that IL-10, besides its immunosuppressive activity, may act as a growth factor for metastatic L-TACB cells. The treatment of L-TACB-bearing rats with a single low-dose cyclophosphamide decreased IL-10 production, reverted immunosuppression and induced the immunologic rejection of tumor metastasis without any effect on primary tumor growth. Our current aim was to investigate the effects of cyclophosphamide on the expression of IL-10 and IL-10R on primary and metastatic L-TACB cells. Considering that cyclophosphamide is a prodrug, we used mafosfamide, a compound that yields in vitro the same active metabolites as cyclophosphamide does in vivo. Mafosfamide induced down-regulation of IL-10 production and IL-10R expression on metastatic cells and, concomitantly, inhibited metastatic cell proliferation. We suggest that mafosfamide would inhibit the regulatory loop mediated by the IL-10/IL-10R system and, as a consequence, metastatic cell proliferation. These results may have a considerable impact on the design of new therapies for metastatic lymphomas.
Keywords: Metastasis; Cyclophosphamide; Cell proliferation